1999
DOI: 10.1034/j.1600-0420.1999.770615.x
|View full text |Cite
|
Sign up to set email alerts
|

The decrease of visual acuity in cataract patients waiting for surgery

Abstract: ABSTRACT.Purpose: To investigate the rapidity of vision loss in eyes waiting for cataract surgery and to estimate what proportion of life expectancy the extended wait for surgery comprised. Methods:The visual acuities at the time of referral and on the day before surgery were compared in 124 patients operated on for cataract in the Vaasa Central Hospital, Finland. The expected survival of the patients after surgery was calculated individually using the Finnish life statistics. Results: During the waiting time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 4 publications
0
18
1
Order By: Relevance
“…We present evidence that vision [6][7][8] and quality of life decreases 8,9 and that the rate of falls increases 9 among patients during the wait period. There is little empirical evidence regarding postoperative outcomes experienced by patients following different lengths of wait times.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We present evidence that vision [6][7][8] and quality of life decreases 8,9 and that the rate of falls increases 9 among patients during the wait period. There is little empirical evidence regarding postoperative outcomes experienced by patients following different lengths of wait times.…”
Section: Discussionmentioning
confidence: 96%
“…6-32 Thirteen of these studies examined the relation between wait time and outcomes, [6][7][8][9][10][11][12][13][14][15][16][17][18] and 19 studies examined the variables that modified this relation.…”
Section: Resultsmentioning
confidence: 99%
“…annum and thus a little slower than the average deterioration shown by Leinonen and Laatikainen (1999). We draw two conclusions from these studies.…”
Section: Tablementioning
confidence: 87%
“…Nevertheless, as was noted earlier, even among patients selected for surgery Leinonen and Laatikainen (1999) found that 48% of patients experienced no or minimal deterioration in an average waiting time of 13 months; it is therefore possible that some of the treated patients both gained little from their surgery and also would not have deteriorated further without surgery.…”
Section: The Effects Of Cataract Surgery On Welfarementioning
confidence: 87%
See 1 more Smart Citation